2001
DOI: 10.1046/j.1365-2133.2001.04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic pemphigus. A report of two cases associated with chronic B-cell lymphocytic leukaemia

Abstract: Paraneoplastic pemphigus (PNP) is an autoimmune blistering and erosive mucocutaneous disease associated with neoplasia. Clinical manifestations are polymorphous, and include erythema, bullae, erythema multiforme-like lesions and severe mucous membrane involvement. PNP manifesting as lichenoid dermatitis has recently been observed. We describe two Italian men with fatal PNP featuring typical PNP autoantigens associated with chronic B-cell lymphocytic leukaemia. The first patient presented with an extensive blis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In the first report of this entity, Anhalt et al 2 emphasized that the IgG deposits in the intercellular spaces were often faint and focal by DIF. Later publications by both Anhalt and Kimyai‐Asadi commented on the negative results of the DIF test in PNP, 5,6 findings that have since been corroborated by other authors 7–11 …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the first report of this entity, Anhalt et al 2 emphasized that the IgG deposits in the intercellular spaces were often faint and focal by DIF. Later publications by both Anhalt and Kimyai‐Asadi commented on the negative results of the DIF test in PNP, 5,6 findings that have since been corroborated by other authors 7–11 …”
Section: Discussionmentioning
confidence: 81%
“…One of these was the presence of immunoglobulin G (IgG) and complement in the epidermal intercellular spaces associated with granular‐linear complement deposition along the epidermal basement membrane zone on direct immunofluorescence (DIF) test 2 . Diagnostic criteria have since been expanded, 3,4 however, and some authors have reported negative DIF results in PNP patients 4–11 . We present three PNP patients who had negative epithelial DIF findings in one or more biopsies, while IgG and/or C3 were observed at the intercellular level in cutaneous adnexa in two cases.…”
mentioning
confidence: 96%
“…The reported patient was also found to have underlying CLL, a common associated malignancy in PNP. 5,6 Using the criteria of Camisa and Helm, 4 this patient met the requirements for a diagnosis of PNP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lichenoid lesions may be present alongside bullous lesions. 77 The lesions of TEN are monomorphous. Acantholysis, a cardinal feature of PNP, is not seen in TEN; and DIF is positive in PNP, but negative in TEN.…”
Section: Histopathology and Differential Diagnosismentioning
confidence: 99%